Constraint is associated with earlier circadian phase and morningness: Confirmation of relationships between personality and circadian phase using a constant routine protocol. (January 2017) - Bullock, B.; Murray, G.; Anderson, J.L.; Cooper-O'Neill, T.; Gooley, J.J.; Cain, S.W.; Lockley, S.W.
Abstract: Associations amongst personality, diurnal preference, and circadian phase were investigated using a constant routine laboratory protocol. One hundred and sixty-eight healthy participants aged 18–30 years (Women n  = 68) completed either a 30- or 50-hour constant routine under dim-light conditions (< 3 lx), during which circadian phase was measured from core body temperature and melatonin. Prior to laboratory admission, self-report measures of personality and diurnal preference were also obtained. The personality trait of Constraint correlated positively with morning diurnal preference and earlier circadian phase, with circadian phase partially mediating the relationship between Constraint and diurnal preference. No other personality variables correlated with circadian phase. Sex was an important covariate in several of the relationships investigated due to lower levels of Constraint and later CBT phase amongst men and was thus controlled for in all relevant analyses. Findings from this highly controlled study are consistent with previous field research in suggesting that earlier circadian phase is associated with the personality trait of Constraint. Highlights: Constraint was associated with Morningness and earlier circadian phase. Morningness was associated with earlier circadian phase and a larger phase angle. Circadian phase partially mediated the relationship between Constraint and Morningness. Sex was an important covariate due to lower levels of Constraint and later circadian phase amongst men.